Muslim Indian Musical Art in Medan - Wafii, Muhammad (KOLABORASI: Journal of Multidisciplinary, 2024)
This thesis is the result of research that describes the history of Muslim Indian music in the city of Medan. The existence of Muslim India in Medan City is of interest to other Medan City people towards Muslim Indians in Medan City. One of the things that makes the people of Medan City interested in Muslim India in the city of Medan is music. As for the background of the author's interest in writing this thesis, this thesis is based on the results of observations and interviews that the author conducted with Muslim Indian cultural and community in Medan City where the author found the fact that the existence of Muslim Indian Music Arts in Medan City was very popular.The research method used is descriptive research method with data collection techniques through field studies which include observation and interviews.The results of the research show that the Indian Muslim Music Arts in the city of Medan is very well liked by the people of the city of Medan and its development is very rapid, it makes the people of the city of Medan memorize songs that use Indian poetry and music.